The impact of the application of Algerian auditing standards on the quality of audit reports -Study applied for a sample of professionals for the year 2018- (Journal of Economic Additions, 2019)
The objective of this study is to know the impact of the application of Algerian auditing standards on the quality of the auditor's reports, and taking into account the fact that these reports have an important information value. The auditor is the eye of the owners of the company. Discovering anomalies or financial corruption and reported in case of justified doubt. To carry out this study, the descriptive method was used interview by a group of Statutory Auditors and bodies related to the preparation and use of Algerian auditing standards during the period (March 2018).The study reported that the commitment to apply Algerian auditing standards in the Algerian accounting environment still needs to be developed in order to be fully compatible with the reality of the Algerian business environment.Key words: tax audit; tax control; tax management; tax costs; tax recovery.